Distance to climate change consequences reduces willingness to engage in low-cost mitigation actions – Results from an experimental online study from Germany - Nicolai Heinz; Ann-Kathrin Koessler; Stefanie Engel (ZBW - Leibniz Information Centre for Economics, 2021)
Adverse consequences of climate change often affect people and places far away from those that have the greatest capacity for mitigation. Several correlational and some experimental studies suggest that the willingness to take mitigation actions may diminish with increasing distance. However, the empirical findings are ambiguous. In order to investigate if and how socio-spatial distance to climate change effects plays a role for the willingness to engage in mitigation actions, we conducted an online experiment with a German population sample (n=383). We find that the willingness to sign a petition for climate protection was significantly reduced when a person in India with a name of Indian origin was affected by flooding as compared to a person in Germany with a name of German origin. Distance did not affect donating money to climate protection or approving of mitigation policies. Our results provide evidence for the existence of a negative effect of distance to climate change consequences on the willingness to engage in low-cost mitigation actions. Investigating explanations for such an effect, we find that it can be attributed to the spatial distance dimension, which reduced participants' perception of being personally affected by climate change. Moreover, we found some cautious evidence that people with strong racist attitudes react differently to the distance manipulations, suggesting a form of environmental racism that could also reduce mitigation action in the case of climate change.
Keywords: D91; C93; Q54; 330; psychological distance; social distance; climate change; spatial distance; mitigation; economic experiment; environmental racism